The Effect Of Work Environment, Organizational Culture And Job Satisfaction On Employee Performance At Pt Valbury Asia Futures, Sleman Yogyakarta - Fredela Juamita Avelinai (Universitas Trunodjoyo Madura, 2025)
satisfaction on employee performance at PT Valbury Asia Futures Sleman Yogyakarta. The population inthis study were employees who worked at PT Valbury Asia Futures using a sample of 66 PT Valbury AsiaFutures employees using the sampling technique used in this research using saturated samples. Theresearch method used in this research uses quantitative methods. Data analysis uses regression analysisThe results of this research show that the work environment, organizational culture and job satisfactionhave a positive and significant effect on employee performance. This research strengthens theories whichstate that work environment factors, organizational culture, and job satisfaction play an important role inbuilding employee performance. The implications of this research are expected to create a conducive workenvironment, build a positive organizational culture, and provide job satisfaction in order to improveemployee performance.Companies also need to design morale-boosting programs that include bonuses,appreciation and respect for employee achievements, in order to increase their dedication andparticipation in realizing organizational targets